A facilitation model based on soft systems methodology to support decision making in brazilian watershed committees. - GOMES JÚNIOR, Alexandre de Araújo. (2021)
This study aimed to propose a facilitation model based on Soft Systems Methodology to support decision-making processes that occur in Brazilian watershed committees. For this, three scientific papers were developed. The first paper presents a literature review, whose objective was to analyze the relevant empirical and theoretical literature about PSMs published over the last decade (2010-2020). In the second paper, we present a literature review, whose objective was to investigate the use of Problem Structuring Methods in Social-Ecological Systems. In these two papers both qualitative and quantitative Content Analysis was used to analyze the data. Thus, with the subsidies provided by these two reviews, the third paper was developed, in which a facilitation model based on Soft Systems Methodology for supporting decision-making processes in Brazilian watershed committees was proposed. Additionally, the facilitation model was used to structure an environmental conflict in Paraíba, Brazil. The model has the potential to be applied as a formal tool for supporting participatory decision-making in Brazilian watershed committees. Therefore, it is considered that this thesis brought contributions both to academic research and to society, as the evolution of the field of PSMs was presented, the way these approaches were applied in Social-Ecological Systems, the way these approaches were applied in Social-Ecological Systems, and the proposed model that can improve decision-making processes on water resources in Brazil.